Safety of Early Discharge Among Low-Risk Patients After Primary Percutaneous Coronary Intervention: An Updated Systematic Review and Meta-Analysis - Sugiharto F; Trisyani Y; Nuraeni A; Songwathana P (Dove Medical Press, 2024)
Firman Sugiharto,1 Yanny Trisyani,2 Aan Nuraeni,2 Praneed Songwathana3 1Master Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 3Faculty of Nursing, Prince of Songkla University, Songkhla, 90110, ThailandCorrespondence: Firman Sugiharto, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +6282218235600, Fax +6282287793411, Email firman17001@mail.unpad.ac.idBackground: Guidelines for early discharge (ED) strategies after primary percutaneous coronary intervention (PPCI) in low-risk patients still need to be informed. Previous meta-analysis evidence is considered to have limitations, from the level of heterogeneity, which is still relatively high, and the sample size still needed to be more significant.Purpose: This study aims to identify the safety of early discharge after PPCI in low-risk patientsMethods: The literature search used five primary databases: CINAHL, PubMed, ScienceDirect, Scopus, Taylor and Francis, and one search engine: Google Scholar. Two reviewers independently screened and critically appraised studies using JBI's and Cochrane's Risk of Bias tool. Fixed and random effects model were applied to collect standardized mean differences and risk differences. Statistical analysis was performed using Review Manager 5.3 and JAMOVI version 2.4.8.0.Results: Seven RCTs consisting of 1.780 patients and seven cohort studies consisting of 46.710 patients were included in the quantitative analysis. The results of the RCT analysis showed no significant differences in all-cause readmission (RD − 0.01; 95% CI: − 0.04 to 0.01; Z=1.20; p=0.23; I2=0%) and mortality (RD 0.00; 95% CI: − 0.01 to 0.01; Z=0.01; p=0.99; I2=0%) and also significant in reducing LOS in hour (SMD − 2.32; 95% CI: − 3.13 to − 1.51; Z=5.64; p< 0.001; I2=93%) and day (SMD − 0.58; 95% CI: - 1.00 to − 0.17; Z=2.76; p=0.006; I2=84%). In addition, analysis of cohort studies showed that ED strategy was associated with all-cause readmission (RD − 0.00; 95% CI: − 0.01 to − 0.00; Z =2.18; p=0.03; I2=0%) and mortality (RD − 0.01; 95% CI: − 0.02 to − 0.00; Z=2.04; p=0.04; I2=94%).Conclusion: ED strategies in low-risk patients after PPCI can be completely safe. This is proven by the absence of significant differences in readmission and mortality rates as well as reduce the length of stay.Keywords: coronary heart disease, early discharge, meta-analysis, PPCI